Prevalence of hepatic steatosis in apparently healthy medical students: a transient elastography study on the basis of a controlled attenuation parameter - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
ObjectiveDespite the increasing burden of nonalcoholic fatty liver disease (NAFLD) in modern societies, the optimal screening method to detect hepatic steatosis in the general population remains to be established. Controlled attenuation parameter (CAP) measured with transient elastography (TE) has recently emerged as a reliable imaging tool for the screening and diagnosis of NAFLD. Here, we sought to investigate the prevalence of TE-defined hepatic steatosis in a sample of apparently healthy medical students. We also assessed the relationships between CAP and traditional NAFLD risk factors.Materials and methodsA total of 112 Turkish medical students (48 women and 64 men, mean age 20.51.1 years) underwent TE. On the basis of previous studies, a cut-off value of 238dB/m for CAP was used for the diagnosis of hepatic steatosis.ResultsOn the basis of the selected cut-off for CAP, we identified 26 students (23.2%) with TE-defined NAFLD. Univariate correlation analyses showed that CAP values were significantly associated with BMI (r=0.40, P<0.001), waist circumference (r=0.39, P<0.001), and hip circumference (r=0.34, P<0.001). In multivariable analysis, only BMI retained its independent association with CAP (=0.36, t=3.4, P<0.001).ConclusionNAFLD is highly prevalent even in apparently healthy young individuals. CAP assessment with TE may be useful for an early, noninvasive identification of hepatic steatosis.
Keywords: controlled attenuation parameter; hepatic steatosis; nonalcoholic fatty liver disease; screening; transient elastography; FATTY LIVER-DISEASE; NONINVASIVE ASSESSMENT; NAFLD; CAP; BIOPSY; FIBROSCAN(R); DIAGNOSIS; FIBROSIS; ADULTS; CARE